2011
DOI: 10.1007/s11136-011-9951-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and health as determinants of quality of life in community-dwelling older adults

Abstract: Abstract:Purpose It is important to understand the determinants of differences in quality of life in old age, and to include a wide range of possible predictors. The present study investigated the determinants of quality of life in two groups of older adults for whom there was an unusually informative set of possible predictor variables. Results Linear regression analyses revealed that HADS depression had the greatest influence on quality of life. Personality traits, most notably Emotional Stability, also pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 57 publications
(86 reference statements)
11
64
3
8
Order By: Relevance
“…In other words, higher neuroticism scores on CI were associated with more frequent reporting of SBS symptoms. New reports using WHOQOL-BREF in a large elderly sample support our fi ndings, stressing the benefi cial role of emotional stability on the subjective estimation of quality of life (18).…”
Section: Relation Between Neuroticism and The Estimation Of Quality Osupporting
confidence: 81%
“…In other words, higher neuroticism scores on CI were associated with more frequent reporting of SBS symptoms. New reports using WHOQOL-BREF in a large elderly sample support our fi ndings, stressing the benefi cial role of emotional stability on the subjective estimation of quality of life (18).…”
Section: Relation Between Neuroticism and The Estimation Of Quality Osupporting
confidence: 81%
“…24 The negative association between quality of life and anxiety and depression symptoms measured by the HADS was also found in the study by Brett et al in a population of 1,641 elderly persons in a linear regression analysis. 18 Depression increases the feeling of functional disability, impairs the quality of social relationships and treatment adherence, and contributes to substantial impairment in the patient's quality of life. 25,26 Our results reinforced that, in a Brazilian sample from a tertiary outpatient clinic, psychiatric symptoms, especially depression, have a negative impact on patients, even considering any variable or medical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have studied determinants of QoL in older adults (Sloane et al 2005;Hoi et al 2010;Brett et al 2012). A national survey on dependency done in Chile in 2010 showed that QoL in the older individuals is influenced by socio-economic and health-related factors, such as education, number of chronic diseases, self-perceived symptoms of depression and difficulties in activities of daily living (ADL), (SENAMA 2010).…”
Section: Introductionmentioning
confidence: 99%